Sequential ordering problems for crane scheduling in port terminals. (10th April 2010) - Montemanni, R.; Smith, D.H.; Rizzoli, A.E.; Gambardella, L.M.
The Sequential Ordering Problem (SOP) is a version of the Asymmetric Travelling Salesman Problem (ATSP) where precedence constraints on vertices are imposed. A tour is feasible if these constraints are respected, and the objective is to find a feasible solution with minimum cost. The SOP models many real world applications, mainly in the fields of transportation and production planning. In particular, it can be used to optimise quay crane assignments. In this paper, we experimentally evaluate the contributions of the basic ingredients of the state-of-the-art algorithm for the SOPs: Local Searches (LSs), ant colony and heuristic manipulation.